The legacy of the king of pinoy rap a photo essay on the analysis of Francis Magalona's songs - Cordova, Rhemaebel, G.; Pagunsan, Auser Jann F.; Paroginog, Christian N. (2016.)
One of the most known rap artists that contributed their nationalistic songs is Francis Magalona (Francis M.). Dubbed as the King of Pinoy Rap, Magalona has produced various songs that talk about Filipino attributes, values and pride (Hal Leonard Corp., 1992). This research endeavoured to identify the recurrent patterns in the songs of Francis Magalona in the categories of culture, nationalism and societal issues. A focus group discussion was held in order to discover if the youth during the time of Francis M?s career peak share the same analysis as that of the results of codebook of the proponents. The proponents of the study, together with the participants of the focus group discussion, interpreted these meanings into photographs. This multi-phased research-based creative work utilized several scientific procedures until the creative results. These procedures are as follows: (a) analysis of the nine chosen songs of Francis Magalona (b) focus group discussion with participants who are fans or indifferent to Francis Magalona (c) execution of photo exhibit that was held in the College of Arts and Sciences in the University of the Philippines Visayas. The analysis of the songs showed that Francis Magalona?s songs contained themes on culture, nationalism and societal issues. Specifically the results showed that seven out of nine songs portrayed culture, seven out of nine songs portrayed nationalism and eight out of nine songs depicted societal issues. The focus group discussion led to the following conclusions: (1) participants determined the Filipino trait of being family oriented (2) nationalism was highly noticed (3) participants only noticed corruption and abuse as societal issues.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Farancis Magalona; Music; Culture; Nationalism; Societal Issues; Photography